In Situ Organ-Specific Vascularization in Tissue Engineering. Issue 8 (August 2018) - Fu, Jiayin; Wang, Dong-An
Abstract : Other than a few avascular tissues, almost all human tissues are connected to the systemic circulation via blood vessels that promote metabolism and function. Accordingly, engineered vascularization is a vital goal in tissue engineering for regenerative medicine. Endothelial cells (ECs) play a central role in vascularization with two significant specificities: physical interfaces between vascular stroma and blood, and phenotypic organ-specificity. Biomaterial scaffolding technologies that address these unique properties of ECs have been developed to promote the vascularization of various engineered tissues, and these have advanced from mimicking vascular architectures ex situ towards promoting spontaneous angiogenic remodeling in situ . Simultaneously, endothelial progenitor cells (EPCs) and organ-specific ECs are attracting more and more attention with the increasing awareness of the diversity of ECs in different organs. Highlights: ECs physically interface between the vascular stroma and blood. ECs not only provide instructive signals for organogenesis but also have organ-specific phenotypes. Biomaterials that can promote spontaneous angiogenic remodeling in situ have been developed to address these unique properties of ECs. In response to physical or biochemical cues from scaffolds, host blood vessels grow into engineered tissues and form functional vascular networks in situ . Because vascularization occurs where engineered tissues are engrafted, in situ angiogenic remodeling ensures that the regenerated vascular networks are organ-specific. Simultaneous, organ-specific vascularization can also be established by vascularizing engineered tissues with endothelial progenitor cells that can differentiate into various endothelial phenotypes or organ-specific ECs.